MON-2, a Golgi protein, promotes longevity by upregulating autophagy through mediating inter-organelle communications - Artan, Murat; Sohn, Jooyeon; Lee, Cheolju; Park, Seung-Yeol; Lee, Seung-Jae, V (Landes Bioscience, 2022)
The Golgi apparatus regulates the process of modification and subcellular localization of macromolecules, including proteins and lipids. Aberrant protein sorting caused by defects in the Golgi leads to various diseases in mammals. However, the role of the Golgi apparatus in organismal longevity remained largely unknown. By employing a quantitative proteomic approach, we demonstrated that MON-2, an evolutionarily conserved Arf-GEF protein implicated in Golgi-to-endosome trafficking, promotes longevity via upregulating macroautophagy/autophagy in C. elegans. Our data using cultured mammalian cells indicate that MON-2 translocates from the Golgi to the endosome under starvation conditions, subsequently increasing autophagic flux by binding LGG-1/GABARAPL2. Thus, Golgi-to-endosome trafficking appears to be an evolutionarily conserved process for the upregulation of autophagy, which contributes to organismal longevity.